Pediatric progressive multifocal leucoencephalopathy presenting with neuroregression in a child with newly diagnosed HIV - Payal Keswaani; Shreya Chauhan; Praveen Kumar (Current Medicine Research and Practice)
Progressive multifocal leucoencephalopathy is a rare demyelinating condition of the central nervous system that results from infection with human polyomavirus 2 commonly referred to as the John Cunningham virus (JCV). The entity has been observed in immunocompromised conditions such as human immunodeficiency virus (HIV) infection, haematological malignancies, post-transplant patients and prolonged steroid use. Although it is very well described in HIV-infected adults, paediatric cases have rarely been reported in the available literature. We report a case of a 9-year-old child who presented with fever, loose stools, abdominal distension and loss of previously acquired milestones. After extensive evaluation, the HIV serology was found to be reactive. When further investigated, the cerebrospinal fluid was found to be positive for the JCV, a finding further supported by the neuroimaging findings.